Design of High-Speed Autonomous Sorting system with GRASP Distribution Algorithm - Sinche, Julio; Arias, Julio; Arce, Diego; Balbuena, Jose; Cuellar, Francisco (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
Courier companies are facing new challenges caused by the increase in daily package deliveries; in addition, clients demand faster service and accurate tracking of packages. Even though, the development of the sorting systems allows high-speed sorting, the optimization of the distribution are a bottle-neck in logistics. Due to this, a customized automation solution needs to be implemented for these companies.The design and development of an elevated high-speed conveyor is proposed for a local courier company. The conveyor is composed by 150 tilting-trays that allows bidirectional classification, also a decentralized control system with internet connection is implemented for updating package states and monitoring the conveyor performance. In order to reduce the package classification time by at least 10%, a metaheuristic algorithm based on a Greedy Randomized Adaptive Search Procedure (GRASP) was developed to optimize container assignment.